MEMBANGUN DUNIA YANG BERANI: MENEGAKKAN KEBERAGAMAN DAN KEMAJEMUKAN DI INDONESIA - Marbun, Saortua (Universitas Wijaya Kusuma Surabaya, 2023)
This article discusses the importance of building a courageous world in upholding diversity and pluralism in Indonesia. Through a literature review method, this research examines various studies and theories relevant to understanding and explaining the importance of diversity and pluralism in social, economic, and political development in Indonesia. The research findings show that diversity and pluralism are wealth that must be appreciated, nurtured, and fought for as part of the nation's identity. By bravely facing diversity and pluralism, we can create a more inclusive, tolerant, and peaceful society. This article also offers effective policy recommendations and strategies for promoting diversity and pluralism in Indonesia, as well as identifying research limitations and directions for further research. Keywords: pluralism, inclusion, tolerance, peace